Optimization of house purchase recommendation system (HPRS) using genetic algorithm - K.A.F.A. Samah; I.M. Badarudin; E.E. Odzaly; K.N. Ismail; N.I.S. Nasarudin; N.F. Tahar; M.H. Khairuddin (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
This paper presents the optimization of house purchase recommendation system (HRPS) using Genetic Algorithm.  Everyone in this world has their own dream house and plan to purchase it depending on their budget and based on the house preferences. Homebuyers face problem in comparing the house property websites according to the factors during the house survey. Subsequently, it is time-consuming in making the decision and they need to bear the transportation cost as they will need to travel to one house developer office to another. In addition, some of the homebuyers felt disappointed when their expectations were not met. Thus, in order to optimize the preferences, in this paper, we present a web-based house purchase recommendation system (HPRS) using a genetic algorithm. Then, it follows by test the functionality and usability of the system. As a result, the system found to function accordingly and obtain more than the average score of system usability scale testing. For further research, it is recommended to add more data to the database and compare with other algorithms.